On the use of field RR Lyrae as galactic probes: V. : optical and radial velocity curve templates - Braga, Vittorio Francesco; Crestani, J.; Fabrizio, Michele; Bono, G.; Sneden, C.; Preston, G. W.; Storm, J.; Kamann, S.; Latour, M.; Lala, Hitesh Narendra; Lemasle, Bertrand; Prudil, Zdeněk; et al. (The astrophysical journal)
We collected the largest spectroscopic catalog of RR Lyrae (RRLs) including ≈20,000 high-, medium-, and lowresolution spectra for ≈10,000 RRLs. We provide the analytical forms of radial velocity curve (RVC) templates. These were built using 36 RRLs (31 fundamental—split into three period bins—and ﬁve ﬁrst-overtone pulsators) with well-sampled RVCs based on three groups of metallic lines (Fe, Mg, Na) and four Balmer lines (Hα, Hβ, Hγ, Hδ). We tackled the long-standing problem of the reference epoch to anchor light-curve and RVC templates. For the V-band, we found that the residuals of the templates anchored to the phase of the mean magnitude along the rising branch are ∼35% to ∼45% smaller than those anchored to the phase of maximum light. For the RVC, we used two independent reference epochs for metallic and Balmer lines and we veriﬁed that the residuals of the RVC templates anchored to the phase of mean RV are from 30% (metallic lines) up to 45% (Balmer lines) smaller than those anchored to the phase of minimum RV. We validated our RVC templates by using both the single-point and the three phase point approaches. We found that barycentric velocities based on our RVC templates are two to three times more accurate than those available in the literature. We applied the current RVC templates to Balmer lines RVs of RRLs in the globular NGC 3201 collected with MUSE at VLT. We found the cluster barycentric RV of Vγ = 496.89 ± 8.37(error) ± 3.43 (standard deviation) km s−1, which agrees well with literature estimates.
Gesehen am 28.04.2022
Keywords: Milchstraßensystem; RR-Lyrae-Stern